PROBLEMS IN USING ICHNOFACIES FOR DEPOSITIONAL ENVIRONMENT INTERPRETATION CASE STUDY: THE CISAAR FORMATION, SUNGAI CISAAR, SUMEDANG DISTRICT, WEST JAVA, INDONESIA - Yan Rizal; Aswan ⠀; Reynaldy Fifariz; Adityan Mulia (BULLETIN OF THE MARINE GEOLOGY, 2021)
Although numerous researchers have used trace fossils method to determine depositional environment, this method is still considered less robust. This is due to the finding of several similar trace fossils in two or more diverse environments, leading to irrelevancy in environmental interpretation. Therefore, we conducted this study in order to verify how powerful the trace fossil analysis is, by applying this method to interpret the depositional environment of the Cisaar Formation in the Cihanyir Tonggoh area, Sumedang Regency, West Java. We combined trace fossil study with foraminiferal assemblage analysis and vertical succession of related sedimentary units. For this study, 19 rock samples that have been collected from outcrop along 16 m traverse and 14 m measured stratigraphic sections were examined.The result of the study shows that shallow marine trace fossils which were developed at the edge of the shelf, were transported into the basin by gravitational mass flow and re-deposited as deep marine turbidites. Trace fossils were generally found in sandstones, while planktonic foraminifers were found in claystones-sandstones interbeds. This study concludes that to avoid inconsistency in the interpretation of the depositional environment, performing trace fossils method must be integrated with other methods, e.g. analysis of lithofacies and biofacies.